Efektivitas Implementasi Hukum Lingkungan dalam Pengelolaan Wilayah Pesisir Berbasis Partisipasi Masyarakat di Kampung Pomako Mimika - Ludia Jemima I.R Reumy; Ruth Kambuaya; Markus Aryasdy Ijie (Jurnal Antologi Hukum, 2026)
This study aims to conduct an in-depth analysis of the effectiveness of environmental law implementation in coastal area management based on community participation in Pomako Village, Mimika Regency. The research method applied is empirical legal research, with field data collection techniques including in-depth interviews, direct observations, and relevant legal document studies. The results reveal that the implementation of environmental law in managing the coastal areas of Pomako Village is currently not running effectively in the field. This condition is caused by several main constraints, including low legal literacy among local communities, a lack of regular socialization programs from the local government, and the suboptimal formal institutional frameworks capable of accommodating indigenous community involvement in decision-making processes. Consequently, natural resource utilization in coastal areas often triggers environmental degradation and potential conflicts of interest. This study recommends the need to strengthen regional regulations that integrate local wisdom and develop sustainable legal assistance programs for the community to achieve resilient and sustainable coastal management.